PENANGANAN PROBLEMATIKA PENGEMIS, GELANDANGAN DAN ORANG TERLANTAR (PGOT) MELALUI BIMBINGAN DAN KONSELING ISLAMI DI BALAI REHABILITASI SOSIAL â€œMARTANIâ€ CILACAP - Zaenal Abidin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2013)
The background of this research is the exixtance of beggars, homelesspeople, and ignored people. Some of them could utilize some facitities from thegovernment, such as rehabilitation office. The government has made a rule toallow them to stay there and get some trainings for only six months. After theyhave spent their time in the rehabilitation office, they have to live in the societyand use their skills they have got from the trainings in the rehabilitation office tosurvive. However, what really happen is that most of them just move from onerehabilitation office to another.This research use descriptive qualitative approach. This research was donein Social Rehabilitation Office Marini, in Cilacap. The research findings showsthat islamic guidance and concelling program is able to increase their ability tolive better and be independent people.